(untitled) (Research, Society and Development, 2021)
Objective: Understand the perception of children, adolescents and family caregivers about the presence of the clown during the hospitalization process. Methodology: qualitative, descriptive exploratory study with 20 participants, five children, five adolescents and 10 family caregivers who experienced the hospitalization process in a pediatric hospital in the West of Santa Catarina, held between August and October 2019. The production of the data included interviews. The data analysis occurred concomitant to the field stage and was in accordance with the content analysis proposed by Bardin. Results: Three thematic categories emerged: The clown as an inspiring force to face the difficulties caused by the hospitalization process: when you are happy everything starts to flow better; the search for strategies for the re-signification of hospitalization: has to breathe and face and the clown as mediator between the hospitalization process and the context of the previous life: I would give anything to be there at home. Conclusion: The performance of this study enabled the understanding that the presence of the clown character in the hospitalization process minimizes the impacts of hospitalization with the offer of playful elements that help in recovery.